El Salvador : Technical Assistance Report-Monthly Volume Indicator of Economic Activity and Institutional Sector Accounts Mission. (IMF Staff Country Reports; Country Report, 2020)
This Technical Assistance report on El Salvador highlights analysis on the Monthly Volume Indicator of Economic Activity (IMVAE) and institutional sector accounts mission. The mission reviewed the process followed by the National Accounts Department team to consolidate the IMVAE and compile the economic activity indicators established in accordance with the recommendations of the previous mission carried out in September 2017. It found a very thorough analysis and review of the basic statistics available for measuring that indicator. Particularly noteworthy is the magnitude of the interinstitutional effort to provide new information gleaned from the results of the Monthly and Quarterly Economic Surveys, conducted by the Directorate General of Statistics and Censuses with Central Reserve Bank of El Salvador support. The mission suggested to continue to apply the methodology established for compiling and continuously updating the IMVAE, while constantly analyzing the consistency, quality, and timeliness of the calculation of the indicator and its alignment with quarterly data and ensuring that it is consistent with the concepts and guidelines underlying Quarterly National Accounts aggregates.